2014
DOI: 10.1155/2014/501392
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Potential of Tinctures from Fruits, Green Husks, and Leaves ofJuglans regiaL.

Abstract: The aim of this study was to assess the phenolic composition and nutraceutical potential of tinctures from fruits in two stages of maturity (F3, younger; F25, older), green husks (GH), and leaves (L) of Juglans regia L. In all extracts gallic, protocatechuic, 3-caffeoylquinic, 3-ρ-coumaroylquinic, 4-caffeoylquinic, 4-ρ-coumaroylquinic, and ρ-coumaric acids and quercetin-3-O-deoxyhexoside were detected using UPLC-MS technique. Caffeic acid hexoside I and quercetin-3-O-deoxyhexoside I have been identified in GH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…Carvalho et al documented that Juglans regia L. leaf extract significantly protected AAPH-induced oxidative hemolysis of human erythrocytes in a time- and concentration-dependent manner [ 12 ]. In another study, the antioxidant potential of ethanolic extract of Juglans regia L. leaves was measured and the highest ability to chelate Fe 2+ , high reducing power, high antiradical activity, and relatively low prevention of lipid oxidation documented [ 37 ]. Results of an in vivo study demonstrated that administration of walnut leaf extract increased the antioxidant enzymes superoxide dismutase and catalase against CCI4-induced oxidative damage in rat liver [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al documented that Juglans regia L. leaf extract significantly protected AAPH-induced oxidative hemolysis of human erythrocytes in a time- and concentration-dependent manner [ 12 ]. In another study, the antioxidant potential of ethanolic extract of Juglans regia L. leaves was measured and the highest ability to chelate Fe 2+ , high reducing power, high antiradical activity, and relatively low prevention of lipid oxidation documented [ 37 ]. Results of an in vivo study demonstrated that administration of walnut leaf extract increased the antioxidant enzymes superoxide dismutase and catalase against CCI4-induced oxidative damage in rat liver [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical profile of Juglans regia green husks is quite variable; however, our findings are in good agreement with the most abundant groups of compounds found in literature for Juglans spp. samples such as phenolic acids and flavonoids (Cosmulescu et al, 2010;Gawlik-Dziki et al, 2014;Stampar et al, 2006), as well as tetralone and naphthalene derivatives (Du et al, 2014;Jin-Hai et al, 2018;Wang et al, 2017). As phenolic compounds (e.g.…”
Section: Phytochemical Composition Of Walnut Husksmentioning
confidence: 99%
“…In another study, phenolic acids and tetralone derivatives were the main compounds identified in samples collected in China, using spectroscopic analysis (UV-Vis, 1H NMR, 13C NMR, 2D NMR, HR-ESI-MS) (Du et al, 2014). Other authors identified phenolic acids and flavonoids during the characterization performed this time by LC-MS (Gawlik-Dziki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the commonly consumed tree nuts includes walnut that belongs to the juglandaceae family. It is one of the oldest grown plants and is distributed worldwide ranking third in nut production after cashews and almonds (Fernandez-Lopez et al 2000).…”
Section: Introductionmentioning
confidence: 99%